Multigenerational effects of paternal spatial training are lasting in the F1 and F2 male offspring. Issue 5 (2nd May 2022) - Riyahi, Javad; Abdoli, Behrouz; Gelfo, Francesca; Petrosini, Laura; Khatami, Leila; Meftahi, Gholam Hossein; Haghparast, Abbas
Abstract : Recent studies on intergenerational transmission of learning and memory performances demonstrated that parental spatial training before fertilization could facilitate learning and memory in the offspring, but many questions remain unclarified. Essential issues regarding whether and how long the effects of parental training in a task can last in several generations, and whether learning a task repeated in the successive generations can enhance a load of multigenerational effects. In the present study, the spatial performances of F1 and F2 generations of male offspring of fathers or grandfathers spatially trained in the Morris Water Maze were evaluated and compared with the performance of a control sample matched for age and sex. Further, to investigate the memory process in F1 and F2 male offspring, brain-derived neurotrophic factor (BDNF), p-ERK1/2 and acetylated histone 3 lysine 14 (H3K14) expression levels in the hippocampus were analyzed. The findings showed that paternal training reduced escape latencies and increased time spent in the target quadrant by F1 and F2 male offspring. Besides, paternal spatial training repeated in two generations did not enhance the beneficial effects on offspring's spatial performances. These findings were supported by neurobiologic data showing that paternal training increased BDNF and p-ERK1/2 in the hippocampus of F1 and F2 male offspring. Furthermore, the hippocampal level of acetylated H3K14 increased in the offspring of spatially trained fathers, reinforcing the hypothesis that the augmented histone acetylation might play an essential role in the inheritance of spatial competence.